Pengaruh Wearable technology terhadap Pembelajaran Kolaboratif dalam Pendidikan Jasmani - Butsiarah, Butsiarah; Suhada, Sitti (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the impact of the use of wearable technology, specifically smartwatches, in improving collaborative learning in Physical Education subjects. Smartwatches function as a direct physical activity monitoring tool, including indicators such as heart rate, number of steps, and duration of activity. This study used a quantitative method with a quasi-experimental design involving 60 high school students, who were divided into an experimental group and a control group. The experimental group used smartwatches during Physical Education learning activities, while the control group followed the learning without the support of such technology. The results obtained showed that the use of smartwatches had a positive impact on increasing social interaction and cooperation among students. This device encouraged active engagement, provided instant feedback, and increased students' awareness of their physical performance, which then became the subject of discussion in group work. In conclusion, the application of smartwatches in the context of Physical Education learning has the potential to strengthen collaboration between students and increase their participation in the learning process.